THE IMPACT OF EPIDEMIES ON THE ECONOMY OF THE WORLD - Kalinichenko, Olena; Poita, Iryna (Zhytomyr Ivan Franko State University, 2020)
The article is devoted to the analysis of patterns and stable trends of the impact of world epidemics on world economy. The relevance of the study of the impact of the pandemic on the economy, as well as the mechanisms of its regulation and stabilization are substantiated. The article explores modern approaches to the impact of epidemics and pandemics on the economies of the world and Ukraine in particular, highlights some of the common aspects that have received greater attention. These pandemics have been shown to be cyclical with recurrence. The epidemic scale and its impact on the world economy are presented, leading to the breaking of economic chains and braking for several months or even one year of economic and social development. The peculiarities of functioning and the main tendencies of changes in the world economy are analyzed. The main features of the current stage of economic development of Ukraine and its impact on pandemics are identified. It is investigated which sectors of the economy undergo the first blow and identify a chain of negative economic effects through the internal and external production and commercial chains, which they were part of. The long-term effects of the impact of the crisis on the Ukrainian economy are considered, a standard set is typical in the crisis period is given. In particular, the economic losses and losses of GDP from pandemics are analyzed. The content of the main factors influencing the economy of Ukraine during the crisis period and the proposed measures of the authorities to improve the current economic situation are revealed. On the basis of the conducted research, an anti-epidemic package of actions for the economy of the country in the domestic and foreign markets was presented. It also identified measures that should somewhat alleviate the burden on business and further stabilize the economic fluctuations caused by the pandemic. Such research is very relevant and important for a thorough understanding of the mechanism for the spread of relevant economic shocks.